Are climate and security policies coherent and integrated in Kenya? A policy coherence analysis. - Schapendonk, Frans; Sarzana, Carolina; Scartozzi, Cesare; Savelli, Adam; Madurga Lopez, Ignacio M.; Pacillo, Grazia; Läderach, Peter R.D. (2023)
This fact sheet assesses the coherence and climate security-sensitivity of policy and strategy documents extracted from sectors relevant to the climate, peace, and security nexus at both the national level in Kenya and regional level across East Africa.